Iran’s educational diplomacy in the Muslim world: activities of Al-Mustafa International University in Malaysia and Afghanistan - Banikamal, Abdolmoghset; Ra'ees, Wahabuddin (SETA Foundation, 2018)
Ayatollah Khomeini, the Islamic Republic of Iran’s spiritual leader, in the immediate days of the 1979 Revolution contemplated promoting of Shi’ite religious doctrinal values in the Muslim World. In Khomeini’s view the Islamic Republic was obliged to design a strategy to effectively instill Shi’ite core doctrinal values in young minds and within the academic community in the largely Sunnite majority Muslim states. Khomeini used the narrative of ‘exporting the revolution’ to attain this objective of the Islamic Republic. The Islamic Republic’s religious sectarian establishment’s strategy of exporting revolution among others focused on educational diplomacy that is sponsoring a host of educational initiatives such as establishment of Jāmicah al-Muṣṭafā al-Cālamīyyah or al-Mustafa International University (MIU) branches and promoting its activities across the Muslim World. MIU is a sizable university with a number of overseas branches operating across the Muslim World. This paper discusses the role of the MIU in the conduct of Islamic Republic’s educational diplomacy in Malaysia and Afghanistan in Iran’s quest for promoting Shi’ite doctrinal values, soft power and greater influence in politics of the Muslim World. A word of caution is in order. Throughout this paper, the terms ‘Irano-Islamic’ or ‘Islamic’ in the Islamic Republic of Iran’s official documents and Iranian literature refers to Shi’ite version of Islam and the declared official ideology of the Islamic Republic of Iran.